Investigating the importance of strain-coupling in lead-free 2–2 relaxor/ferroelectric composites with digital image correlation. (1st July 2022) - Martin, Alexander; Maier, Juliana G; Streich, Friedemann; Kamlah, Marc; Webber, Kyle G
Abstract: Ceramic–ceramic composite structures are a viable solution to improve the electromechanical response of lead-free ferroelectrics (FEs) through tuning of the local electrical and mechanical fields. The origin of the enhanced properties, however, remains unclear, as many of the possible effects, such as polarization and strain coupling (PSC) as well as interface diffusion, are interrelated and difficult to separate or directly investigate. In this study, we use a custom-built digital image correlation system to directly investigate the influence of strain coupling on 2–2 composites consisting of 0.90Na1/2 Bi1/2 TiO3 –0.06BaTiO3 –0.04K0.5 Na0.5 NbO3 (NBT–6BT–4KNN) and 0.94Na1/2 Bi1/2 TiO3 –0.06BaTiO3 (NBT–6BT) by varying the mechanical interface contacts between end members. Specifically, two model cases were utilized to separate the relative contributions of the PSC mechanisms: (a) electrically connected and (b) mechanically and electrically connected. The local strain gradient was characterized through the thickness of the composite across different layers as well as the interface, where the macroscopic large signal longitudinal and transverse FE response was determined. Experimental results reveal an enhancement of the large signal piezoelectric coefficient d 33 ∗ by approximately 10% from 390 to 440 pm V −1 due to strain coupling.